TanDEM-X for mass balance of glaciers and subglacial volcanic activities - Floricioiu, Dana; Abdel Jaber, Wael; Minet, Christian; Rossi, Cristian; Eineder, Michael (2015 IEEE International Geoscience and Remote Sensing Symposium (IGARSS), 2015)
The TanDEM-X satellite mission through its bistatic formation provides high horizontal and vertical resolution topographic data. Multi temporal TanDEM-X acquisitions allow short term analysis of variations of the earth surface elevation which in turn can be converted to volume changes. We are investigating the capabilities of the TanDEM-X data to detect and map short term changes at glacier surfaces in two different situations. One study case is Jorge Montt outlet glacier of the South Patagonia Icefield known for its accelerated mass depletion and front retreat. The second example is located on the Vatnajökull Ice Cap in Iceland and is related to the activity of the Bárðarbunga volcanic system in summer 2014 as a consequence of climate driven depletion as well as due to volcanic activities below the ice surface.